PECULIARITIES OF METABOLIC PARAMETERS IN THE HEALING OF WOUNDS COMPLICATED BY EXPERIMENTAL CHRONIC KIDNEY DISEASE - Pavlov, S.B.; Kumetchko, M.V.; Babenko, N.M.; Litvinova, O.B.; Valilshchykov, M.V.; Babaieva, O.I. (World of Medicine and Biology, 2021)
The work is devoted to the study of the features of changes in the main indicators of metabolic processes during the healing of experimental wounds complicated by chronic kidney disease. Histological examination showed a significant violation of the morphological and functional state of the kidneys in rats with chronic kidney disease. There was a decrease in the levels of glucose, urea, uric acid in the blood serum of experimental animals 1 week after the infliction of wounds in comparison with similar indicators of animals in the control group. In rats, 4 weeks after surgery, the concentration of urea and uric acid remained reduced, while the glucose level almost recovered to the level of the control group, and the creatinine content significantly increased in comparison with the control. Inflammatory processes in the renal tissue lead to metabolic disorders during the healing of wounds complicated by chronic kidney disease, which is reflected by statistically significant changes in the levels of biochemical parameters.